Genocide and resistance Nr. 33(1) - Tininis, Vytautas; Bagušauskas , Juozapas Romualdas; Veilentienė, Audronė; Mikelevičius , Laimis; Burinskaitė, Kristina; Ereminas, Gintautas (Genocidas ir rezistencija, 2013)
Full Issue